Advances in solid-phase extraction techniques: Role of nanosorbents for the enrichment of antibiotics for analytical quantification - Suseela M.N.L.; Viswanadh M.K.; Mehata A.K.; Priya V.; Vikas; Setia A.; Malik A.K.; Gokul P.; Selvin J.; Muthu M.S. (My University, 2025)
Antibiotics are life-saving medications for treating bacterial infections; however it has been discovered that resistance developed by bacteria against these incredible agents is the primary contributing factor to rising global mortality rates. The fundamental cause of the emergence of antibiotic resistance in bacteria is the presence of antibiotic residues in various environmental matrices. Although antibiotics are present in diluted form in environmental matrices like water, consistent exposure of bacteria to these minute levels is enough for the resistance to develop. So, identifying these tiny concentrations of numerous antibiotics in various and complicated matrices will be a crucial step in controlling their disposal in those matrices. Solid phase extraction, a popular and customizable extraction technology, was developed according to the aspirations of the researchers. It is a unique alternative technique that could be implemented either alone or in combination with other approaches at different stages because of the multitude of sorbent varieties and techniques. Initially, sorbents are utilized for extraction in their natural state. The basic sorbent has been modified over time with nanoparticles and multilayer sorbents, which have indeed helped to accomplish the desired extraction efficiencies. Among the current traditional extraction techniques such as liquid-liquid extraction, protein precipitation, and salting out techniques, solid-phase extractions (SPE) with nanosorbents are most productive because, they can be automated, selective, and can be integrated with other extraction techniques. This review aims to provide a broad overview of advancements and developments in sorbents with a specific emphasis on the applications of SPE techniques used for antibiotic detection and quantification in various matrices in the last two decades. © 2023 Elsevier B.V.